Development of a biodegradable and eco-friendly novel printing composite using biomaterials on textile substrate and assessing the characterization - Abdullah Al Tahsin; Tonmoy Saha; Satu Saha; Sukarna Saha; Faishal Ahamed (Scientific Reports)
Abstract The use of biomaterials has grown in interest over the past few years for their unique properties and diverse applications. The textile printing industry is one of the appropriate sectors to introduce biomaterials that can replace synthetic printing ingredients and reduce environmental threats. In this research, a novel textile printing process was developed using a combination of eco-friendly printing ingredients and later applied with screen printing technology on different textile substrates such as cotton, poly-cotton (65% polyester and 35% cotton), and linen. To evaluate the performance of different printed fabrics, spectrophotometric and color fastness properties were assessed and compared against the conventionally printed control samples. The CIE L*a*b* values showed a slight difference in color intensity between conventional and sustainable printing. For non-washed samples, a prominent fastness result of the highest rating was observed for sustainable-printed specimens. The results were also consistent with the number of washings, as 10 times washed samples also showed comparatively better results in the fastness property and color staining. This eco-friendly printing can replace detrimental synthetic ingredients without compromising the environment, performance, or effectiveness and sustainable printing is a potentially feasible and suitable alternative to conventional printing.